Competitive advantages through clusters : An empirical study with evidence from China - Šarić, Saša (Strategisches Kompetenz-Management, 2012)
How do firms create competitive advantages through clusters? To show what successful cluster-firms are made up of, Saša Šarić makes use of a rigorous exploratory approach combining a thorough theory review with insights gained from two empirical studies conducted in China. His findings suggest that successful cluster-firms use their Entrepreneurial Orientation to seek out promising new opportunities and exploit their value generating potential through a dedicated Cluster-Capability. Both strategic elements are implemented through high decentralization of decision authority and low task formalization thus requiring highly skilled personnel and entrepreneurial leaders. With his research, the author gives an answer on how firms create competitive advantages through the clusters they are located in. This serves as an important orientation for executives, authorities, and other stakeholders who are interested in making the most out of their local economic environment.